Desain Kaos Sebagai Promosi Wisata di Kabupaten Ngawi - Choirul Wicaksono, Hafish; Henny Lukitasari, Evelyne; Yulianto, Arif (JURNAL KEMADHA, 2023)
ABSTRACT Tourism is a way to relieve fatigue from daily activities and functions as an educational activity in some issues. However, all tourist attractions in Indonesia are not well known by local and foreign tourists. Bali dominates the destination of foreign tourists because it offers cultural tourism and natural beauty different from other regions in Indonesia, such as tourism from Ngawi Regency in East Java. They are not well known to the public, so it views less of visitors. The study aims to design a t-shirt concept as a tourism promotion medium in Ngawi Regency and to design a t-shirt as a tourism promotion medium in Ngawi Regency. The result of designing this Ngawi tourism t- shirt illustration is in the form of the main media, namely Ngawi tourism t-shirts and supporting media, namely Instagram feeds, posters, roll banners, hoodies, catalogues, hats, tote bags, stickers, waist bags, and instruction cards. Supporting media was created to expand the dissemination of information regarding the existence of T-shirts and the design of Ngawi tourism illustrations. Various supporting media can increase public awareness and interest in the design. It makes Ngawi very suitable to be used as a tourism place and can also provide opportunities for its people to sell unique souvenirs to attract tourists' attention. Keywords: Ngawi tourism t-shirt design